Modelagem probabilística para previsão do tempo de iniciação da corrosão por cloretos em estruturas de concreto armado expostas em zonas de atmosfera marinha - Ferreira, Pablo Ramon Rodrigues (2022)
The deterioration of reinforced concrete structures is a common problem in coastal areas. This type of environment is characterized by the action of chloride ions, which after being transported through the air, penetrate the concrete and accumulate close to the reinforcement, initiating the corrosion process. The need for efficient constructions, preventive maintenances and repairs demonstrates the lack of a reliable prediction model of chloride penetration, capable of estimating the service life of these structures. Thus, this work presents a probabilistic model to predict the time of initiation to corrosion in structures of reinforced concrete constructed in zone of marine atmosphere. The model considers the stochastic nature of the corrosion process, seasonal variation of the climatological conditions, the capacity of chloride binding of the cement paste, the conditions of transport of chlorides in unsaturated condition, the solar radiation effect, washout effect and the hydration time of concrete. With an illustrative example, the factors that govern the degradation process were studied. The results show the importance of considering the unpredictability related to design parameters, property of the materials, simplifications of the mathematical model and the environmental conditions of exposure in unsaturated reinforced concrete structures. Finally, the results were validated by comparative analysis with data from the literature and a generalist model for concrete in a marine atmosphere zone is presented.